Uniqueness and predictability in evolution and the history of mollusks - Geerat J. Vermeij; Tracy J. Thomson (Proceedings of the National Academy of Sciences, 2026)
Evolution is a historical process whose trajectories are determined in part by the introduction of new phenotypes. Although most phenotypes have evolved repeatedly within and among clades of organisms, others are unique and apparently originated only once, and even the earliest occurrences of repeated traits were unique for their time. To investigate the timing and circumstances of these unique events, we compiled adult skeletal phenotypes with single origins and first occurrences of repeated traits as recorded in the fossil record in the phylum Mollusca. Of the 24 unique and 72 repeated traits we considered, 46 (48%) originated during the first 96 m.y. of molluscan history (frequency 1 per 2.1 m.y.) and only 50 in the 444 m.y. since then (frequency 1 per 8.9 m.y.), with secondary peaks of frequency in the Triassic and Cenozoic. We interpret this finding to mean that molluscan evolutionary history has become substantially more predictable over time despite increasing diversity. Expansions of the phylum from its ancestral marine epifaunal benthic environment to other habitats including fresh water and dry land were generally not associated with unique or earliest occurrences of repeated phenotypes. Most of the innovations enhanced individual defense or activity and were therefore honed by interactions within and among species, although it remains possible that they originated in temporarily permissive conditions in which genetic and other constraints were relaxed.